Are Extracted Materials Truly Representative of Original Samples? Impact of C18 Extraction on CDOM Optical and Chemical Properties - Andrew, Andrea A.; Del Vecchio, Rossana; Zhang, Yi; Subramaniam, Ajit; Blough, Neil V. (Frontiers in Chemistry, 2016)
Some properties of dissolved organic matter (DOM) and chromophoric dissolved organic matter (CDOM) can be easily measured directly on whole waters, while others require sample concentration and removal of natural salts. To increase CDOM content and eliminate salts, solid phase extraction is often employed. Biases following extraction and elution are inevitable, thus raising the question of how truly representative the extracted material is of the original. In this context, we investigated the wavelength dependence of extraction efficiency for C18 cartridges with respect to CDOM optical properties using samples obtained from the Middle Atlantic Bight (MAB) and the Equatorial Atlantic Ocean (EAO). Further, we compared the optical changes of C18 extracts and the corresponding whole water following chemical reduction with sodium borohydride (NaBH4). C18 cartridges preferentially extracted long-wavelength absorbing/emitting material for samples impacted by riverine input. Extraction efficiency overall decreased with offshore distance away from riverine input. Spectral slopes of C18-OM samples were also almost always lower than those of their corresponding CDOM samples supporting the preferential extraction of higher molecular weight absorbing material. The wavelength dependence of the optical properties (absorption, fluorescence emission and quantum yield) of the original water samples and their corresponding extracted material were very similar. C18 extracts and corresponding water samples further exhibited comparable optical changes following NaBH4 reduction, thus suggesting a similarity in nature (structure) of the optically active extracted material, independent of geographical locale. Altogether, these data suggested a strong similarity between C18 extracts and corresponding whole waters, thus indicating that extracts are representative of the CDOM content of original waters.